2020
DOI: 10.17159/2309-8309/2020/v19n2a5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Soft tissue Projection in Injured NEcks (CSPINE) - Prevertebral soft tissue measurement in paediatric cervical spine trauma

Abstract: Background: In paediatric trauma, measured increase in prevertebral soft tissue thickness on a lateral cervical spine (C-spine) X-ray is interpreted as swelling, raising suspicion of C-spine injury. Defining swelling in absolute measurements is cumbersome-children's sizes vary. Published recommendations are largely lacking in evidence. There may be potentially more consistent tools, for example, to measure soft tissue thickness as a ratio of vertebral body width. The aim of this study was to determine whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…The second study investigated the utility of prevertebral soft tissue to vertebral body width ratios as a single diagnostic tool in the identification of pediatric cervical spine trauma. Similar to our study, the authors found that this ratio had poor sensitivity (33.3% C2 and 44.4% C6) as a stand-alone diagnostic tool 31…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The second study investigated the utility of prevertebral soft tissue to vertebral body width ratios as a single diagnostic tool in the identification of pediatric cervical spine trauma. Similar to our study, the authors found that this ratio had poor sensitivity (33.3% C2 and 44.4% C6) as a stand-alone diagnostic tool 31…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our study, the authors found that this ratio had poor sensitivity (33.3% C2 and 44.4% C6) as a stand-alone diagnostic tool. 31 Analysis of the relationship between PVST dimensions and anatomic variations of the injuries was consistent with previous studies. 24,26,27 Injuries to the anterior column (13/24, 54%) resulted in increased PVST dimensions more often than the posterior column (2/7, 29%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations